2020
DOI: 10.1121/10.0002173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of word class on speaker-dependent information in the Standard Dutch vowel /aː/

Abstract: Linguistic structure co-determines how a speech sound is produced. This study therefore investigated whether the speaker-dependent information in the vowel [aː] varies when uttered in different word classes. From two spontaneous speech corpora, [aː] tokens were sampled and annotated for word class (content, function word). This was done for 50 male adult speakers of Standard Dutch in face-to-face speech (N = 3,128 tokens), and another 50 male adult speakers in telephone speech (N = 3,136 tokens). First, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This type of analysis was not used in the current work because of the relatively small number of speakers and because LR models do not allow for the inclusion of interactions with linguistic factors in the modeling of acoustic-phonetic features. It is unclear how the current results would compare to LR speaker classification, but one study reports that small differences in speaker classification obtained with multinomial logistic regression are not maintained in an LR analysis (Heeren, 2020). It was suggested that this may be caused by differences in the weighting of between-and within-speaker variation in these two methods.…”
Section: Discussionmentioning
confidence: 86%
“…This type of analysis was not used in the current work because of the relatively small number of speakers and because LR models do not allow for the inclusion of interactions with linguistic factors in the modeling of acoustic-phonetic features. It is unclear how the current results would compare to LR speaker classification, but one study reports that small differences in speaker classification obtained with multinomial logistic regression are not maintained in an LR analysis (Heeren, 2020). It was suggested that this may be caused by differences in the weighting of between-and within-speaker variation in these two methods.…”
Section: Discussionmentioning
confidence: 86%